Essential CVS - Vesperman, Jennifer (O'Reilly, 2006)
This easy-to-follow reference shows a variety of professionals how to use the Concurrent Versions System (CVS), the open source tool that lets you manage versions of anything stored in files. Ideal for software developers tracking different versions of the same code, this new edition has been expanded to explain common usages of CVS for system administrators, project managers, software architects, user-interface (UI) specialists, graphic designers and others. Current for version 1.12, Essential CVS, 2nd Edition offers an overview of CVS, explains the core concepts, and describes the commands th.